Analisis hubungan modal sosial terhadap keberdayaan petani pada kelompok tani padi sawah di Desa Jatibaru Kecamatan Bunga Raya Kabupaten Siak - Cepriadi Cepriadi; Kausar Kausar; Rita Suharti (Unri Conference Series: Community Engagement, 2022)
The existence of social capital is very important in agricultural development. The purpose of building social capital is to strengthen community empowerment to become a civil society, the community empowerment approach implies that humans are placed in the position of actors and beneficiaries of the process of finding solutions and achieving development results. Strong social capital will ensure sustainability in building a sense of trust within the community, especially group members. The main idea of empowerment is related to the concepts of social capital and power. Power is often associated and associated with the ability of individuals to make individuals do what they want, regardless of their desires and interests. This study aims to examine the relationship of social capital to the empowerment of farmer groups in Jatibaru Village, Bunga Raya District, Siak Regency. The analysis of this research uses the Spearman Rank Correlation method. Based on the results of the research, the Spearman Rank Correlation value of social capital on farmer empowerment in lowland rice farmer groups in Jatibaru Village obtained a sig (2-tailed) value of (0.000 < 0.05) so it can be concluded that social capital has a relationship with farmer empowerment in rice farmer groups. ricefield. The correlation coefficient value is 0.656 where this value is included in the category of a strong relationship.